Analisis Pengendalian Persediaan Barang Dagang terhadap Penjualan Celana Casual Pada Konter Cardinal Casual Matahari Opi Mall Palembang - Iin Hendrayani (P3M STIE Mulia Darma Pratama, 2020)
Inventory Control is an activity aimed at making inventory or stock far from shortage and can be maintained at optimal level so that the cost of inventory can be optimal. In this research the author discusses the